If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + 30 = 33 Reorder the terms: 30 + 9m = 33 Solving 30 + 9m = 33 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 9m = 33 + -30 Combine like terms: 30 + -30 = 0 0 + 9m = 33 + -30 9m = 33 + -30 Combine like terms: 33 + -30 = 3 9m = 3 Divide each side by '9'. m = 0.3333333333 Simplifying m = 0.3333333333
| 6x(6x-5)-3(5-6x)= | | x^2+23-39=0 | | 16z^4-81z^4=0 | | a^2+6a+36=0 | | 6+ln(x+5)=8 | | Xsquared+5cubed=9cubed | | 9x^4-16=10x^2-17 | | 8x-18=36-6x | | 3*(15-x)=18 | | 2(3x-1)=4 | | 3*(x-15)=18 | | 5(7m-3)=14(2m+5) | | 3*(x-15)=48 | | V=6(8x+2)(5x-4)-10(5x-4) | | (2y-1)dy=(3x^2+1)dx | | 4x=190 | | (2y-1)dy=(3x+1)dx | | 2ln(5x+1)=14 | | 12a-11=15a-10 | | 10z+4=1 | | 3(x+4)-12x=48 | | lnx=70.0173683 | | 2q+5y+4z=0 | | 8h-24=36 | | 12x-11=15x-10 | | 12=(n-1)(n-2)(n-3)(n-4)(n-5)-3n^2 | | -36=y-5y-21 | | 12=(n-1)(n-2)(n-3)(n-4)-(2n^3) | | 12=n^4-12n^3+35n^2-50n+24 | | 8+4x=7x | | -11-5X=-111 | | (y+3)2=25 |